Graduate employability Post-COVID 19: the challenge for Malaysian public university / Muhammad Asiff Rafani Mohd Noor Azmi ... [et al.] - Mohd Noor Azmi, Muhammad Asiff Rafani; Ahmad Bakri, Nur Ashma Hidayah; Aminuddin, Adnan (2021)
The COVID-19 pandemic has led to a dramatic loss of human life worldwide and presents an unprecedented challenge to public health, food systems and the world of work. The pandemic has decimated jobs and placed millions of livelihoods at risk. As breadwinners lose jobs, fall ill and die, the food security and nutrition of millions of women and men are under threat, with those in low-income countries, particularly the most marginalized populations, which include small-scale farmers and indigenous peoples, being hardest hit. Employability refers to someone’s ability to gain initial employment, maintain employment, and obtain new employment if required. “Employability is having a set of skills, knowledge, understanding and personal attributes that make a person more likely to choose and secure occupations in which they can be satisfied and successful (Dacre Pool & Sewell 2007). Graduate employability means the ability of the graduate to get and stay in the job to be able to adapt to the needs of the industry. Furthermore, the job market increasingly demanding graduates to compete, and they need to possess a variety of skills to market their capabilities and academic qualifications. Employability among Malaysian graduates has always been the subject of great societal interest and concern. Malaysia introduced several phases of movement control order due to pandemic COVID-19 since March. Due to this restriction, it is not just affecting the economic activities of the existing employer and employees but it also affecting the work of interns.